Sustainability Disclosure from Capital Structure and Firm Size: Does Independent Commissioner Matter? - Putri, Nada Nabila; Firmansyah, Amrie (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2023)
This study examines whether capital structure and firm size affect sustainability disclosure. In addition, this study also examines the moderating role of independent commissioners in the relationship between the independent and dependent variables. This study employs data from financial statements, annual reports, and sustainability reports of consumer goods industry companies listed on the Indonesia Stock Exchange from 2017 to 2020. The data sources are derived from www.idx.co.id and www.idnfinancial.com and the company's official website. Based on purposive sampling, the total sample used in this study is 148 observations. Hypothesis testing is done by using multiple linear analyses for panel data. The results suggest that capital structure is not associated with sustainability disclosure, while firm size is positively associated with sustainability disclosure. This study also finds that independent commissioners fail to weaken the negative effect of capital structure on sustainability disclosure nor the positive effect of firm size and sustainability disclosure. This study has complemented the literature on the importance of sustainability disclosure as nonfinancial disclosure in the financial accounting research context.